Distributive pattern of aero-allergen sensitivity among patients with naso-bronchial allergy in a tertiary care center of North India (Bangladesh Journal of Otorhinolaryngology, 2024)
Objective: The aims of our study are to determine the pattern of allergen sensitivity among patients with Naso-bronchial allergy and to determine the difference between the pattern of allergen sensitivity among 3 groups- Bronchial asthmas, allergic rhinitis, and bronchial asthma with allergic rhinitis.Methodology: A total of 50 patients with nasobronchial allergy who had either presented to the OPD of the Department of Respiratory Medicine or were referred from the Otorhinolaryngology Department fulfilling the inclusion criteria were included in this prospective observational study conducted from June 2019 to June 2021. A total of 48 antigens were used on 50 patients for Skin prick testing and results were recorded.Result: We observed that all allergens showed positive results however significant positive reaction was seen most commonly in House dust mites (37.3%) and insects (26%) followed by Dust (22.6%), and Dander (20%).Conclusion: Our study concludes that the variation in the prevalence of allergen reactivities in different regions is due to different geo-climatic conditions and adaptation of specific microbiological flora and fauna to a specific climate, pollution, and lifestyle change.Bangladesh J Otorhinolaryngology 2023; 29(2): 55-66